225. TREATMENT OF ANASTOMOTIC LEAK AFTER ESOPHAGECTOMY (TENTACLE– ESOPHAGUS) STUDY: EFFICACY OF DIFFERENT INITIAL TREATMENT STRATEGIES FOR ANASTOMOTIC LEAK. (24th September 2022) - Ubels, Sander; Verstegen, Moniek; Bouwense, Stefan; Hannink, Gerjon; Siersema, Peter; Klarenbeek, Bastiaan; van Workum, Frans; Rosman, Camiel; ,
Abstract: Anastomotic leak (AL) is a common and severe complication after esophagectomy. The presentation of AL is diverse and various treatments are available. However, it is unknown which treatment strategy for which type of leak is most effective. We aimed to investigate the effectiveness of different primary treatments of AL after esophagectomy. TENTACLE—Esophagus is an international retrospective cohort study in 71 centers from 20 countries, which included patients with anastomotic leak after esophagectomy between 2011 and 2019. Detailed data were collected regarding leak characteristics and treatment. Primary outcome was 90-day mortality. Different leak types were defined, i.e., local symptoms (i.e., no intrathoracic fluid collections and well-perfused conduit), intrathoracic fluid collections and conduit ischemia/necrosis. Efficacy of different primary treatment strategies were assessed for these leak types, adjusted for case-mix and leak severity. The full study protocol is accessible at www.tentaclestudy.com . In total, 1509 patients with AL were included and overall 90-day mortality was 11.7%. Of all patients, 482 patients had only local symptoms, 725 patients had intrathoracic fluid collections and 148 patients had conduit ischemia/necrosis. Primary treatment strategies included supportive treatment only (n = 335), drainage (n = 590), defect closure (n = 67), drainage & defect closure (n = 289) and surgical resection of the conduit & esophageal diversion (n = 57). The efficacy of different primary leak treatment strategies is currently being assessed. Results on the efficacy of primary treatment strategies for AL will be ready for presentation at the ISDE meeting. This is the largest study on effectiveness of AL treatments. The final results on efficacy of primary leak treatments will be available for presentation at the ISDE meeting in Tokyo and can offer guidance in clinical practice to determine the preferred primary treatment strategy in patients with anastomotic leak after esophagectomy.